2016
DOI: 10.1139/cjps-2015-0120
|View full text |Cite
|
Sign up to set email alerts
|

Using remote sensing to understand Pinot noir vineyard variability in Ontario

Abstract: The study objective was to determine whether multispectral high spatial resolution airborne imagery could be used to segregate zones in Pinot noir vineyards to target highest quality fruit for premium winemaking. We hypothesized that remotely sensed data would be correlated with vine size and leaf water potential (ψ), and by extension with yield and berry composition. In 2008-2009, multispectral (blue, green, red, near-infrared) airborne images were acquired from four Ontario Pinot noir vineyards (four dates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
(46 reference statements)
4
19
1
Order By: Relevance
“…This positive effect of bunch shading on anthocyanins was demonstrated by Bonilla et al ., who found a positive correlation between NDVI and anthocyanins. However, similar to the present study, other studies have reported a negative correlation between this index and color and the anthocyanin composition of grapes . This suggests that vigor influence on anthocyanin accumulation essentially depends on environmental factors and especially on maximal temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This positive effect of bunch shading on anthocyanins was demonstrated by Bonilla et al ., who found a positive correlation between NDVI and anthocyanins. However, similar to the present study, other studies have reported a negative correlation between this index and color and the anthocyanin composition of grapes . This suggests that vigor influence on anthocyanin accumulation essentially depends on environmental factors and especially on maximal temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…However, similar to the present study, other studies have reported a negative correlation between this index and color and the anthocyanin composition of grapes. 47 This suggests that vigor influence on anthocyanin accumulation essentially depends on environmental factors and especially on maximal temperatures. Furthermore, Ledderhof et al 47 also found a negative correlation between NDVI and total phenols in grapes, which suggests that not only anthocyanins, but also other phenolic compounds of grapes could be related to this index.…”
Section: Relationships At the Grape Scalementioning
confidence: 99%
See 1 more Smart Citation
“…However, use of aircraft-based RS is costly and in agricultural systems it can be imprecise [5]. Data must be converted to vegetation indices (VIs), e.g., normalized difference vegetative index (NDVI) through appropriate computer software [12][13][14][15]. Validation of data acquired by RS is necessary to determine whether ostensibly-unique zones are relevant from a standpoint of physiology, yield, and berry composition.…”
Section: Introductionmentioning
confidence: 99%
“…E3S Web of Conferences 50, 02010 (2018) https://doi.org/10.1051/e3sconf/20185002010 XII Congreso Internacional Terroir Aircraft-based RS has been proven useful for monitoring vegetative growth, and for making inferences about grape composition from multispectral measurements. In Ontario, NDVI data from RS was associated with numerous variables in Riesling [14,15] and Pinot noir [13] vineyards, including vine water status, yield components, and berry composition. RS was useful to determine Pinot noir anthocyanins and phenols, in addition to water status, yield and vine size [13].…”
Section: Introductionmentioning
confidence: 99%